WRITTEN STATEMENT OF PHILIP MORRIS, INC. BEFORE THE ASSEMBLY LABOR COMMITTEE RE: AB13 930303 - LANG,J (Tufts Archival Research Center, 2007)
Statement of Joe Lang on behalf of Philip Morris before the Assembly Labor Committee regarding AB13. Praises AB13 for its preemptive qualities but argues it does not balance the interests of smokers and nonsmokers. Criticizes bill for its economic impacts and for obscuring the issue of bad indoor air quality.